HAPPINES-VIRTUE PROBLEMS IN KANT’S "THE CRITIQUE OF PURE REASON" - Nerija Putinaitė (Problemos)
Kant defines ethics as a theory of pure practical reason and virtue, as a disposition to the accomplishment of moral law. Happines is, for him, an empirical determinant of behaviour and it cannot only be the first, but also the passible determinant of behaviour. The human being is distinctive according to the principle of reason that Kant asserts to be of primary and supreme significance. With its judgement, reason oversteps the limits of the empirical world (and happiness) and discovers the unconditional totality of its objects, as suprema good establishes the indispensable identity of happiness with virtue.